Telaah Integratif Pendekatan Linguistik dan Tradisional Terhadap Kaidah Ibdal dalam Derivasi Kata Arab - Kamilatun Nazilla (Pusat riset dan Inovasi Nasional, 2025)
This study aims to analyze the ibdal rule in Arabic word derivation with an integrative approach between traditional methods and modern linguistics. The ibdal rule, namely the change of one letter into another letter in a word, has long been a concern in classical Arabic studies. The traditional approach views ibdal as part of an effort to maintain the purity and beauty of the Arabic language, based on oral history, analysis of ancient poetry, and readings of the Qur'an. Meanwhile, modern linguistics views ibdal as a rational phonological phenomenon, occurring due to phonetic considerations, ease of articulation, and social dynamics. Through an integrative study, this study found that a comprehensive understanding of ibdal can only be achieved by combining an appreciation of classical Arabic heritage with scientific analysis based on modern phonology and morphology. The results of this study indicate that ibdal is not only linguistic, but also reflects the vitality of the Arabic language in responding to changes in the times. The integration of these two approaches also has an impact on the development of curriculum, teaching methods, and the expansion of Arabic language research space towards a more interdisciplinary direction. This study emphasizes the importance of building a scientific attitude that respects tradition while being open to renewal in Arabic studies. Thus, it is hoped that this research can be a significant contribution to the development of Arabic linguistic studies in a contemporary academic context.